2021
DOI: 10.1136/gutjnl-2020-322473
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between diet and gut microbiome, and circulating concentrations of trimethylamine N-oxide: findings from a longitudinal cohort of US men

Abstract: ObjectivesGut-produced trimethylamine N-oxide (TMAO) is postulated as a possible link between red meat intake and poor cardiometabolic health. We investigated whether gut microbiome could modify associations of dietary precursors with TMAO concentrations and cardiometabolic risk markers among free-living individuals.DesignWe collected up to two pairs of faecal samples (n=925) and two blood samples (n=473), 6 months apart, from 307 healthy men in the Men’s Lifestyle Validation Study. Diet was assessed repeatedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
52
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 41 publications
16
52
3
Order By: Relevance
“…For example, C . citroniae has been positively associated with production of trimethylamine N-oxide (TMAO), which is a compound likely connected to intake of red meat ( 26 ). The direct association between red meat intake and type 2 diabetes risk has been known for >15 years ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, C . citroniae has been positively associated with production of trimethylamine N-oxide (TMAO), which is a compound likely connected to intake of red meat ( 26 ). The direct association between red meat intake and type 2 diabetes risk has been known for >15 years ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…TMA is carried through the portal circulation to the liver, where it is oxidized by the host hepatic flavin monooxygenase (FMO) to produce TMAO which is then released into circulation and eventually eliminated in the kidney (64)(65)(66). Consequently, TMAO is dependent upon dietary consumption of precursors, gut microbial enzymatic activity and host genetics (67), and may be a vital mediator among diet, gut microbiota metabolism and the risk of CRC.…”
Section: Tmao and Crcmentioning
confidence: 99%
“…As vegetarians had a low baseline TMAO, and likely have, in the long-term, nurtured non-TMAO producing gut microbiota, the shift to a vegan diet did not alter their TMAO. A previous study found that nonvegetarians are ten times more likely to be high TMAO producers than vegetarians upon carnitine challenge tests, despite no difference in fasting TMAO ( 17 , 44 ) and these may be related to the presence of specific gut species ( 44 , 45 ). Collectively, these results suggest that a vegan diet may be particularly beneficial for high TMAO producers.…”
Section: Discussionmentioning
confidence: 89%